2002
DOI: 10.1038/emm.2002.47
|View full text |Cite
|
Sign up to set email alerts
|

Dual effect of oxidative stress on NF-κB activation in HeLa cells

Abstract: Reactive oxygen species (ROS) has been implicated as an inducer of NF-kappaB activity in numbers of cell types where exposure of cells to ROS such as H(2)O(2) leads to NF-kappaB activation. In contrast, exposure to oxidative stress in certain cell types induced reduction of tumor necrosis factor (TNF)- induced NF-kappaB activation. And various thiol-modifying agents including gold compounds and cyclopentenone prostaglandins inhibit NF-kappaB activation by blocking IkappaB kinase (IKK). To understand such confl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 2 publications
1
59
0
1
Order By: Relevance
“…regulation of IKK and NF-kB is cell-type restricted, but the molecular mechanisms for the astrocytespecific NF-kB pathway are not known (Schreck et al, 1991;Meyer et al, 1993;Anderson et al, 1994;Manna et al, 1998;Li and Karin, 1999;Byun et al, 2002). In the present study, we show that OGD injury activates the transcription factor NF-kB through phosphorylation of IkBa, which finally promotes cell death and COX-2 expression in mouse primary astrocytes.…”
Section: Discussionmentioning
confidence: 45%
“…regulation of IKK and NF-kB is cell-type restricted, but the molecular mechanisms for the astrocytespecific NF-kB pathway are not known (Schreck et al, 1991;Meyer et al, 1993;Anderson et al, 1994;Manna et al, 1998;Li and Karin, 1999;Byun et al, 2002). In the present study, we show that OGD injury activates the transcription factor NF-kB through phosphorylation of IkBa, which finally promotes cell death and COX-2 expression in mouse primary astrocytes.…”
Section: Discussionmentioning
confidence: 45%
“…Both pathways regulate cell survival and death (33), and now have been implicated in carcinogenesis (34,35). In addition to the classical IKKmediated NF-B activation, it has been shown that certain novel pathway can activate NF-B by IKK-independent such as UV and hydrogen peroxide (H 2 O 2 ) induced NF-B activation (36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%
“…Substitution of Cys-179 with alanine was carried out by site-directed mutagenesis as described previously (Jeon et al, 2003 Cell culture, IKK assay and reporter assay HEK-293 and HeLa cells were obtained from the American Type Culture Collection (Manassa, VA), and maintained in DMEM supplemented with 10% heat-inactivated FBS, and antibiotics. Cells were transfected with expression vectors for IKKβ and their mutants using Fugene 6 (Roche Molecular Biochemicals, Mannheim, Germany) and incubated for 48 h. Preparation of cytoplasmic extracts and immunoprecipitation were performed as described (Byun et al, 2002). Kinase activity was measured in reaction mixtures containing 10 µM ATP, [γ-32 P]ATP (2-5 µCi) and GST-IκBα (1 µg) (Jeon et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Phosphorylated GST-IκBα was visualized by autoradiography and quantitated in a phosphor image analyzer (Fujifilm, Tokyo, Japan). Proteins in the cell extracts were analyzed by immunoblotting using ECL system (Amersham Biosciences, Buckinghamshire, U.K.) (Byun et al, 2002). NF-κB reporter gene assay was performed in HeLa cells as described previously (Byun et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation